Solidification - Esther Ares, Alicia (IntechOpen, 2018)
Almost all processing of technologically important materials includes a process where liquid material is cooled to form a solid, called "solidification." In order to form a solid from an undercooled melt, the formation of crystalline nuclei and growth of these nuclei to form a solid are necessary. The process of an atom jumping from the liquid to the solid is a diffusive jump with a driving force. The book Solidification is logically developed through a careful presentation of the relevant theories and models of solidification occurring in a variety of materials. Mathematicians, chemists, physicists, and engineers concerned with melting/freezing phenomena will also find this book to be valuable.